Disease control priorities related to mental, neurological, developmental and substance abuse disorders - Bellows, Nicole; Brayne, Carol; Chandra, Vijay; Chisholm, Dan (World Health Organization, 2006)
The chapters cover mental disorders, neurological disorders, learning and developmental disabilities, and alcohol and illicit opiate abuse. The purpose of this special package is to provide information on cost-effectiveness of inteventions for these specific groups of disorders. This information is intended to contribute to reformulation of policies and programmes and reallocation of resources, eventually leading to reduction of morbidity and mortality.